2017
DOI: 10.30868/ei.v5i10.6
|View full text |Cite
|
Sign up to set email alerts
|

Pendidikan Karakter Berbasis Kearifan Lokal

Abstract: Kearifan lokal yang terdapat pada beberapa kelompok/ masyarakat adat di Indonesia banyak mengandung nilai luhur budaya bangsa yang masih kuat menjadi identitas karakter warga masyarakatnya. Namun disisi lain, nilai kearifan lokal sering kali diabaikan, karena dianggap tidak sesuai dengan perkembangan zamannya. Padahal dari kearifan lokal tersebut dapat di promosikan nilai-nilai luhur yang bisa dijadikan model dalam pengembangan budaya bangsa Indonesia. Dalam konteks inilah studi lapangan ini dilaksanakan untuk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
49

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 0 publications
1
26
0
49
Order By: Relevance
“…This identifier sometimes becomes a link between cultural acculturations even if it is only in the form of language the study of which in Japan showed the existence of language acquisition issues by Latin American students studying in Public Schools in Japan to achieve their academic goals [17]. Synergizing local wisdom values for character education is an important agenda in educational programs where opportunities must be opened to continue to explore the noble values of local culture that are close to the society so that later more massive dissemination can be performed both at national and international levels [1], [5], [18], [19]. Research in Texas showed that character education was strongly encouraged to inspire students to make positive changes in their lives and treat each other with kindness and compassion [20].…”
Section: Discussionmentioning
confidence: 99%
“…This identifier sometimes becomes a link between cultural acculturations even if it is only in the form of language the study of which in Japan showed the existence of language acquisition issues by Latin American students studying in Public Schools in Japan to achieve their academic goals [17]. Synergizing local wisdom values for character education is an important agenda in educational programs where opportunities must be opened to continue to explore the noble values of local culture that are close to the society so that later more massive dissemination can be performed both at national and international levels [1], [5], [18], [19]. Research in Texas showed that character education was strongly encouraged to inspire students to make positive changes in their lives and treat each other with kindness and compassion [20].…”
Section: Discussionmentioning
confidence: 99%
“…Quawas, (2014) persoalan gender dalam cerpen di Arab yang berkaitan dengan dinamika politik, sosial, budaya, dan ekonomi. (Priyatna, 2017) perempuan pekerja di Indonesia dengan kontruksi ketidakadilan gender dan jenis kelamin. Seharusnya perempuan membangun kembali kontruksi feminis dan memperoleh upaya patriarki laki-laki sebagai agen, penguasa, subjektivitas dan intelegensi.…”
Section: Potretunclassified
“…Hal ini mengingat gender pada umumnya erat kaitanya dengan relasi laki-laki dengan perempuan baik dalam aspek sosial politik, ekonomi, maupun budaya (Rusmadi, 2017). Sehubungan dengan hal ini (Latifi, 2016;Margono, 2015;Priyatna, 2017) mengkaji tentang pendidikan gender dalam cerpen. Perempuan dalam karya sastra tidak jauh berbeda dengan realitas karena realitas yang ada dalam karya sastra merupakan perwujudan representasi kenyataan.…”
Section: Potretunclassified
“…The first, they should keep the preservation of traditional values held so that the identity and cultural practices are not exploited by foreign culture. Secondly, they should raise public awareness to explore and understand the values contained in customs (Priyatna 2017). The local values in the development of character education can later be introduced and re-applied specifically in shaping the almost forgotten character education of Kerinci community.…”
Section: Introductionmentioning
confidence: 99%